THE CORRELATION BETWEEN THE SEVERITY OF LIVER CIRRHOSIS WITH ESOPHAGEAL VARICES IN RSUD DR SOETOMO SURABAYA - Deva Medisika Hertiti; Poernomo Boedi Setiawan; Gwenny Ichsan Prabowo (Universitas Airlangga, 2022)
Introduction: Liver cirrhosis is the end stage of chronic liver disease. The morbidity and mortality associated with complications of liver cirrhosis are very high. In cases of death caused by cirrhosis of the liver, it tends to increase from around 676,000 in 1980 to more than one million in 2010, globally equivalent to 2% of all mortality in the world (Mokdad et al., 2014). The mortality rate increases if there are complications such as ascites, hepatic encephalopathy, esophageal varices, and liver cancer, with success rates of 20-60%, 50%, 70-90% (D'Amico, 2014). In liver cirrhosis with esophageal varices, it is reported that patients with mild and severe liver cirrhosis risk 40% and 85% for varicose veins. So, this research is to determine the correlation between the severity of liver cirrhosis with esophageal varices in Dr. Soetomo General Hospital Surabaya. Methods: This study was an analytic observational with a cross-sectional study design. The research subjects used in this study were patients diagnosed with liver cirrhosis with esophageal varices from January 2015 - December 2016. Data were collected from medical records and analyzed using the spearman correlation test. Sampling was carried out in total sampling. Results: Of 26 subjects, most of the subjects were men (69.32%), the highest severity of liver cirrhosis from the Child B group (53.85%), and the highest esophageal varices were grade II and III (46,15%). The most results from each group based on the severity of liver cirrhosis were Child A with grade II esophageal varices (66.7%), and Child B with grade II esophageal varices (64.3%), and Child C with esophageal varices grade III esophagus (88.9%). A correlation coefficient was obtained at 0.659 (p <0.005). Conclusion: This research concludes a significant correlation between the severity of liver cirrhosis and esophageal varices.